2021
DOI: 10.1038/s41598-021-89009-6
|View full text |Cite
|
Sign up to set email alerts
|

Dominant egg surface bacteria of Holotrichia oblita (Coleoptera: Scarabaeidae) inhibit the multiplication of Bacillus thuringiensis and Beauveria bassiana

Abstract: Holotrichia oblita (Coleoptera: Scarabaeidae) and some other scarab beetles are the main soil-dwelling pests in China. Bacillus thuringiensis (Bt) and Beauveria bassiana (Bb) are entomopathogens that have been used as biocontrol agents of various pests. However, scarab larvae especially H. oblita exhibited strong adaptability to these pathogens. Compared to other scarabs, H. oblita could form a specific soil egg case (SEC) structure surrounding its eggs, and young larvae complete the initial development proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Bacterial community composition was analyzed by amplicon sequencing of the 16S rRNA gene V4 hypervariable region with the universal primer set 515F/806R [23]. PCR was carried out as follows: initial denaturation at 95 • C for 10 min, 35 cycles at 94 • C for 1 min, 55 • C for 1 min, and 72 • C for 1 min, and final extension at 72 • C for 10 min.…”
Section: High-throughput Sequencing (Hts) and Bioinformatic Analysesmentioning
confidence: 99%
“…Bacterial community composition was analyzed by amplicon sequencing of the 16S rRNA gene V4 hypervariable region with the universal primer set 515F/806R [23]. PCR was carried out as follows: initial denaturation at 95 • C for 10 min, 35 cycles at 94 • C for 1 min, 55 • C for 1 min, and 72 • C for 1 min, and final extension at 72 • C for 10 min.…”
Section: High-throughput Sequencing (Hts) and Bioinformatic Analysesmentioning
confidence: 99%
“…A stable microbial community is critical for organism health [ 26 ]. The microbial communities on living organisms are always challenged by both invasive [ 21 ] and opportunistic pathogens [ 27 ]. Beauveria bassiana is an invasive species, in contrast to the normal migratory locust microbial community in the microenvironment of the locust.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence of different strains of the same pathogenic fungi to the same host can sometimes be very different [ 28 ]; just like the results obtained in the LT50 test, the virulence of strain BbZJ1 to locusts was significantly stronger than that of strains BbBJ and BbHN1. Changes in virulence factors in fungi due to gene mutation [ 29 , 30 ] and immune differences among host individuals possibly explain this variation in virulence [ 27 , 31 ]. Previous studies have shown that microbial communities play key roles in the health and development of their multicellular hosts and are an important part of the arthropod immune system [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation